2016
DOI: 10.1186/s12711-016-0196-y
|View full text |Cite|
|
Sign up to set email alerts
|

Population structure and genome characterization of local pig breeds in Russia, Belorussia, Kazakhstan and Ukraine

Abstract: BackgroundIt is generally accepted that domestication of pigs took place in multiple locations across Eurasia; the breeds that originated in Europe and Asia have been well studied. However, the genetic structure of pig breeds from Russia, Belorussia, Kazakhstan and Ukraine, which represent large geographical areas and diverse climatic zones in Eurasia, remains largely unknown.ResultsThis study provides the first genomic survey of 170 pigs representing 13 breeds from Russia, Belorussia, Kazakhstan and Ukraine; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
10
28
0
1
Order By: Relevance
“…; Traspov et al . ). Five breeds from North China (Min, Hetao Daer, Laiwu, Bamei and Gansu Tibetan), especially Min, displayed a signature of admixture with European breeds, as evidenced by their paraphyletic grouping patterns in the NJ tree (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…; Traspov et al . ). Five breeds from North China (Min, Hetao Daer, Laiwu, Bamei and Gansu Tibetan), especially Min, displayed a signature of admixture with European breeds, as evidenced by their paraphyletic grouping patterns in the NJ tree (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The white phenotype of the Rongchang pig is a recessive trait (Lai et al, 2007) and there is high conservation-related interest in investigating the origin of the PW breed. Knowledge of the genetic structure, based on genomic data, has been important in revealing the demographic and evolutionary history of pig breeds worldwide (Ai et al, 2013;Herrero-Medrano et al, 2013;Pham et al, 2014;Traspov et al, 2016). However, to date, the genetic structure of PW has scarcely been investigated, despite the specific, desirable qualities of this breed, including high prolificacy, high meat quality and good adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implied that the genetic distance of pig breeds from China may be influenced by their geographical distribution (Megens et al, 2008;Traspov et al, 2016). Thus, for further exploration of the relationship between PW and Taihu pig breeds may benefit from the inclusion of more breeds distributed in the area adjacent to Pudong.…”
Section: Discussionmentioning
confidence: 99%
“…Among the European commercial breeds Duroc, Landrace, and Yorkshire, two AHR gene copies were detected in 46.1, 67.0, and 66.9%, respectively, of the tested population. Previous studies indicated the Landrace and Large White were much more closely related than Duroc at the genome-wide level [54,55], thus the higher proportion in Landrace and Yorkshire compared to Duroc could be attributed to the differences in the genome level among the three breeds. Landrace and Yorkshire were commonly used as maternal pigs, which are selected in the artificial breeding process based on large litter size.…”
Section: The Copy Number Of Ahr Gene Is Associated With Pig's Litter mentioning
confidence: 98%